MOTIF DAN KEPUASAN GENERASI Z KOTA DENPASAR MENGGUNAKAN VIDIO SEBAGAI APLIKASI VIDEO STREAMING (E-Jurnal Medium, 2022)
Vidio is a video sharing website, this site allows users to upload, watch and share videos. Video can be used on internet-connected devices, such as smartphone, tablet, and also on smart TV. Vidio is a video streaming application service. This study aims to find out what the motives of Generation Z of Denpasar City are using Vidio as a video streaming application and how satisfaction is obtained by Generation Z of Denpasar City in using Vidio as a video streaming application. The subjects of this research are Generation Z in Denpasar City with the years of birth 1997-2012. Denpasar City was chosen because Denpasar City is listed as the city that has the highest number of internet users in Bali Province. In this study, using the motives proposed by Dennis McQuail, namely information motives, personal identity motives, social integration and interaction motives, and entertainment motives. The theory used in this research is Uses and Gratifications Theory. This research uses descriptive quantitative method with purposive sampling technique. Data collection was obtained by distributing questionnaires using a likert scale. The results of this study indicate that there is one of four motives that can be satisfied from using video, namely the motive of integration and social interaction, while the information motive, personal identity motive, and entertainment motive have not been able to be satisfied. Keywords: Motive, Satisfaction, Generation Z, Vidio